Effect of preservatives on extending the shelf-life of Rasogolla (Chemical Engineering Research Bulletin, 2010)
The study aims, to find out an effective preservative to extend the shelf-life of Rasogolla, a highly popular Bengal sweetmeat achieving the highest worth in all social and religious festivals in Bangladesh due to its special appeal of taste, as well as to assess the effect of preservative on its biochemical and microbial status. Rasogolla available in local market survives for too a short span (2-3days) to export in abroad since its processing and preservation still lie at a very infantile stage. In this research, Rasogolla was prepared in laboratory using calcium propionate, sodium metabisulfite, sorbic acid, sodium diacetate, sodium propionate, acetic acid, benzoic acid, sodium benzoate, butylated hydroxytoluene, butylated hydroxyanisole, P-4-hydroxybenzoate as preservatives followed by a comparative study on the biochemical and microbial status of both market and laboratory made Rasogolla. Sorbic acid and sodium metabisulfite exerted the highest effectiveness in extending Rasogolla’s shelf-life for 24 and 15 days, respectively, whereas the combination of sorbic acid (0.1%) and sodium metabisulfite (0.1%) was found more effective than their individual uses rendering the longer keeping ability up to 30 days ensuring color, flavor, taste and texture. Compositional analysis showed that total solid, moisture, fat, protein, carbohydrate and ash content of market Rasogolla were 75.87-83.17%, 16.83-24.13%, 2.86-4.31%, 5.2-7.94%, 64.26-73.30% and 0.30-0.61%, respectively, whereas those in laboratory made were 73.70-79.83%, 20.17-26.30%, 3.18-6.09% 6.9-8.59%, 61.18-65.25% and 0.30-0.61%, respectively. Market Rasogolla were found more susceptible for microbial growth and contamination than that prepared in laboratory.Keywords: Rasogolla, Preservative, Sorbic acid, Channa, Na-metabisulfiteDOI = 10.3329/cerb.v14i1.3940 Chemical Engineering Research Bulletin 14 (2010) 19-24